Editorial: it will go away!? pandemic crisis and business in Asia - Ting, Hiram; Ling, Jeffrey; Cheah, Jun Hwa (Asia Business Research Corporation, 2020)
In this Editorial we look into the lessons business in Asia can learn and certain opportunities academics and practitioners can tap into during the COVID-19 pandemic. We also look at some of the plausible things marketers and those who are going into business using online platforms can do during the crisis. Given the magnitude of the pandemic, business strategies and activities need to be reconsidered. Although the lessons and approaches presented in the Editorial are not entirely new, especially to those in digital marketing, business technology and innovation, they have to be evaluated and planned out in a new light. Despite the devastating effect of the crisis, it is hoped that the Editorial will shed some ideas and perpetuate the discourse about the moving forward of business in Asia at these times.